Contained Herniated Lumbar Disc: CT- and Fluoroscopy-Guided Automated Percutaneous Discectomy—A Revival - Amoretti, Nicolas; Gallo, Giacomo; Nicolas, Stacoffe; Federico, Torre; Theumann, Nicolas; Guinebert, Sylvain; Thouvenin, Yann; Cornelis, François; Hauger, Olivier (Seminars in Interventional Radiology, 2018)
The combination of a new device and dual guidance (computed tomography [CT] and fluoroscopy) is similar to other percutaneous devices in achieving a mechanical decompression of the disc. The difference, however, is that the target of the decompression with the current technique is the herniated disc itself. The goal of this combined technique is to create a space, an “olive” around the probe, allowing a decrease in pressure inside the hernia. Percutaneous discectomy under combined CT and fluoroscopic guidance is a minimally invasive spine surgery that should be considered as an alternative to surgery in properly selected patients.
Keywords: percutaneous; discectomy; computed tomography; disc herniation; fluoroscopy; spine; interventional radiology